"Trauma Makes You": An Interview with Donovan O. Schaefer. (20th May 2016) - Schaefer, Donovan; Sheedy, Matt; Rein, Nathan
Abstract : Matt Sheedy (U. of Manitoba) and Nathan Rein (Ursinus Coll.) interview Donovan O. Schaefer (Trinity Coll., Oxon.) about his 2015 book, Religious Affects: Animality, Evolution, and Power.